Article RETRACTED due to manipulation by the authors Comparative analysis of plyometric training alone and plyometric training combined with static stretching on vertical jump in non-athlete students - Bizimana Jean-Berchmans; Ilham Ilham; Tomoliyus Tomoliyus; Vlad Adrian Geantă; Japhet Ndayisenga; Novadri Ayubi; Heru Andika; Bekir Erhan Orhan; Glady Sukma Perdana; Fredrik Alfrets Makadada; Eduard Emor Kumenap; Yuliana Sattu; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to evaluate and compare the effects of plyometric training alone versus plyometric training combined with static stretching on vertical jump performance in untrained students enrolled in their third year of Sciences and Techniques of Physical Activities and Sports (STAPS). A total of 45 participants, including 9 females aged between 21 and 23 years, were randomly assigned to one of three groups: two experimental groups and one control group, each comprising 15 subjects. The participants had an average age of 23 ± 1.17 years, a body mass of 57 ± 5.84 kg, and a height of 1.69 ± 0.07 meters. Prior to the intervention, all subjects underwent baseline vertical jump testing using a Myotest device, which simultaneously recorded jump height, speed, and the power and strength of the lower limb muscles. After an 8-week training period, these parameters were re-evaluated. Results indicated a significant improvement in vertical jump height, speed, and lower limb strength and power across plyometric training alone (GE1) and a group undergoing plyometric training combined with static stretching (GE2) (p≤ 0.05). Notably, the group undergoing plyometric training combined with static stretching exhibited significantly superior results compared to the group receiving plyometric training alone (p<0.05). These findings suggest that integrating static stretching with plyometric training yields more substantial enhancements in vertical jump performance for novice STAPS students.